Cost and value management in projects / Ray R Venkataraman, Jeffrey K Pinto - Venkataraman, Ray R
Cost and Value Management in Projects provides practicing managers with a thorough understanding of the various dimensions of cost and value in projects, along with the factors that impact them, and the managerial approaches that would be most effective for achieving cost efficiency and value optimization. This book addresses cost from a strategic perspective, offering thorough coverage of the various elements of value management such as value planning, value engineering and value analysis from the perspective of projects.